Energy focusing in shock-collapsed bubble arrays. (10th October 2020) - Bempedelis, N.; Ventikos, Y.
Abstract: Abstract : During its collapse a bubble can draw and concentrate energy from its surroundings. In the present work, we investigate the behaviour of certain multibubble configurations that have the potential for achieving significant levels of energy focusing. The dynamics of these configurations are studied for the first time in three dimensions, and are shown to be significantly different from those in two dimensions. Novel observations regarding focusing regimes in collapsing arrays are presented. Finally, through a series of numerical experiments on previously unexplored arrangements, we demonstrate that substantially enhanced levels of energy concentration can be achieved.